Application of change of direction deficit to evaluate cutting ability - Cuthbert, M.; Thomas, C.; dos Santos, T.; Jones, P. A. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to examine the application of the change of direction deficit (CODD) to a 90° cut test to examine whether CODD provides a unique evaluation of an individual's cutting ability. Thirty-six male collegiate team-sport (23 Rugby/13 Soccer) athletes (age: 20 ± 1.4 years; height: 1.80 ± 0.08 m; mass: 83 ± 13.2 kg) participated in the study. Each athlete performed 3 trials of a 20-m sprint (with 5 and 10 m splits) and 2 change of direction (COD) tests (90° cut and 505 tests) cutting/turning from both legs. Completion times for all sprint and COD tests were measured using timing cells. For both COD tests, CODD was determined (COD completion time—10 m sprint time). Pearson correlation was used to explore the relationships between sprint times and CODD and completion times. Significant (p < 0.001) moderate-to-large (r = 0.467) correlations between sprint times and 90° cut completion times for left and right cuts were observed. Nonsignificant (p > 0.05) trivial-to-small correlations (r = 0.199) were found between sprint variables and 90° cut CODD. Significant (p < 0.001) large to very large correlations (r = 0.531) were revealed between the left and right 90° cut and 90° cut CODD. The results suggest that the CODD could be applied to isolate and assess the cutting ability in COD speed tests that involve a single cutting maneuver. Failure to inspect CODD could lead to incorrect evaluation of an athletes cutting or COD ability.